2003
DOI: 10.1074/jbc.c300135200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Post-translational Modification of Tryptophan Residues in Cardiac Mitochondrial Proteins

Abstract: We examined the distribution of N-formylkynurenine, a product of the dioxidation of tryptophan residues in proteins, throughout the human heart mitochondrial proteome. This oxidized amino acid is associated with a distinct subset of proteins, including an over-representation of complex I subunits as well as complex V subunits and enzymes involved in redox metabolism. No relationship was observed between the tryptophan modification and methionine oxidation, a known artifact of sample handling. As the mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
131
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(136 citation statements)
references
References 26 publications
(9 reference statements)
3
131
1
1
Order By: Relevance
“…This was most dramatic in paraquat treatments but was also evident in the environmental stresses. This damage was more evident in chilling than in drought treatments (note especially Spots 4,5,6,8,9, and 10) despite chilling seeming to be the milder stress based on the data presented in Figs. 1 and 2.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…This was most dramatic in paraquat treatments but was also evident in the environmental stresses. This damage was more evident in chilling than in drought treatments (note especially Spots 4,5,6,8,9, and 10) despite chilling seeming to be the milder stress based on the data presented in Figs. 1 and 2.…”
Section: Figmentioning
confidence: 99%
“…A series of studies have analyzed the detailed sites of protein oxidation in mitochondria from various organisms under control conditions and following in vitro oxidation protocols. These reveal that a complex array of oxidative modifications occur, including carbonyl group formation (3,4), oxidation of tryptophan (5), tyrosine nitration (6), and oxidative modification of enzyme cofactors such as lipoic acid (7). Concomitant with imposed oxidative damage, specific proteins are either synthesized or lost from mitochondria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Complex 1 of the OxPhos pathway has been shown to be affected by I/R [20,[90][91][92][93], whereby the activity of the complex is significantly reduced, with concurrent changes in the abundance of several complex 1 subunits, as identified by proteomic techniques including 2-DE [76,94]. To investigate the discrete compositional alterations with I/R, isolated mitochondria treated with elevated levels of ROS and/or NO resulted in the inactivation of complex 1 [95][96][97][98][99][100][101], with in vitro preparations showing a similar inactivation of complex 1 by increased concentration of both ROS and Ca 21 [102]. Sadek et al [102] showed that function was restored when Ca 21 levels diminished and NADH was present.…”
Section: Changes In Mitochondrial Function and Protein Abundancementioning
confidence: 99%
“…These particular peptides were selected based on their signal intensities and absence of methionine, tryptophan, and cysteine residues. The presence of these residues is not desirable because they tend to be reactive and are prone to oxidation which would modify the peptide's molecular mass (52)(53)(54), leading to inconsistent MRM analyses. Stable 15 N isotope bacteriophage labeling was achieved by inoculating the wild-type bacteriophage with a 15 N-enriched broth, producing a stable isotope-labeled bacteriophage 53 internal standard.…”
Section: Resultsmentioning
confidence: 99%